A Partocracy with Chinese Characteristics: Governance System Reform under Xi Jinping. Issue 126 (1st November 2020) - Guo, Baogang
ABSTRACT: Regime resilience is a frequent theme in Chinese political research. This article examines China's latest effort to enhance the regime's political stability by modernizing its governance system. It argues that China's current governance system reform has institutionalized the Chinese party-state and transformed it into a partocracy. Partocracy, as a new analytical model, can be very useful but is still underdeveloped. The case presented in this article will reveal some of the main features of the emerging Chinese partocracy. It shows that the governance system reform undertook by Xi Jinping has begun the process of institutionalizing, rationalizing, and legalizing the old party-state system. By examining these latest developments, the author hopes to stimulate more interest in the study of partocracy as an analytic model.